Continuous monitoring of concrete E-modulus since casting based on modal identification: a case study for in-situ application - Azenha, Miguel (2012)
An in situ application of a recently developed technique for continuous measurement of concrete E-modulus since casting is addressed in this paper. Such technique is based on the continuous modal identification of a composite beam that contains the material under test. As concrete hardens, the flexural resonant frequency of the beam increases and the computation of E-modulus can be made with recourse to the beam’s equation of motion. Even though recent publications have shown the feasibility of this technique in laboratory environment, no actual in situ application has been tested so far. That is one of the topics of this paper, which also proposes improvements to the originally devised method and compares results with ultra-sound wave velocity measurements. The scope of the work is extended with the modal analysis of a prefabricated beam made of the same concrete under test, allowing insights to be made regarding the E-modulus of concrete.